Performance of fuel cells using biogas and its sensitivity analysis. (2022) - Naveena Shree, M.; Hareesh Krishnan, H.; Glivin, Godwin; Jaganathan, V.M.; Premalatha, M.; Mariappan, V.; Sekhar, Joseph
Abstract: The use of renewable fuels has been currently increased since the non-renewable sources of energy are depleting. H₂ is one of the main energy carriers which can be derived from various renewable and non-renewable fuels. Biogas has high methane content and that can be converted to H₂ using reforming reaction followed by water–gas shift reaction. The main objective of this study is to optimize H₂ yield by using autothermal reforming followed by the water–gas shift reaction and preferential oxidation and to analyze the performance of polymer electrolyte membrane fuel cell under different operating parameters. Sensitivity analysis using methane, steam and air flowrate, conversion of methane and oxygen, reactor temperature and pressure on the yield of H₂ and carbon-monoxide yield has been performed. The H₂ yield obtained from Autothermal reactor is 64.73 % which is increased to the value of 75.21 % after the preferential oxidation reactor. The H₂ yield achieved after the optimization is 68.64 % from the Autothermal reactor. The Optimum Air/Steam/Feed ratio obtained is 1:2.23:4.60. H₂ is produced at the rate of 330 kg/hr. Results showed that Polymer Electrolyte Membrane fuel cell efficiency and stack consumption is decreased with the increase in fuel flowrate. There is slight variation in polymer electrolyte membrane fuel cell efficiency and stack consumption with the increase in fuel and air supply pressure. Stack efficiency remained constant with increasing fuel and oxidant composition. Polymer Electrolyte Membrane fuel cell operates effectively at both the temperatures of 65 °C and 600 °C.